Analisis Komparatif Produksi Dan Pendapatan Usahatani Jagung Dengan Berbagai Kombinasi Pupuk Anorganik Di Desa Beka Kecamatan Marawola Kabupaten Sigi - Risky Risky; Made Antara; Effendy Effendy (Universitas Tadulako, 2018)
ABSTRACK This study aimed to determine the income of corn farming system, and the significant differences between the corn production and the farming system income under various combinations of inorganic fertilizers. The location of the study was determined purposively and was carried out in September to October 2017. The determination of the respondents was selected by the Proportioned Stratified Random Sampling technique. The number of farmer samples was stratified based on the use of combination of inorganic fertilizers in which a group of 13 people combined Urea with KCl whereas the other group of 17 people combined Urea with NPK. The analysis tool used in this research was the analysis of farm income and comparative analysis. The results showed that the average income of the farmers using the combination of Urea and KCl fertilizers was IDR 6,244,900.45 while those farmers using the combination of Urea and NPK fertilizers was IDR 7,665,322.03. Hypothesis testing on the comparison of the production and the income of the farmers using the combination of Urea and KCl fertilizers and those using the combination of Urea and NPK fertilizer showed the t-count value equal to 7.07 and 5.47, respectively, with α 5% and t-table of 2.048 suggesting that there is a significant difference between the two combinations used by the farmers in Beka village, Marawola sub district of Sigi district. Keywords : Comparative and income analysis, Corn, and inorganic fertilizer.